1986
DOI: 10.1002/j.1939-4640.1986.tb00937.x
|View full text |Cite
|
Sign up to set email alerts
|

Different Testosterone and LH Relationships in Infertile Men

Abstract: In both man and animals, changes in Leydig cell structure and function accompany seminiferous tubule damage. In this study of 1745 men attending an infertility clinic, 14% of men with elevated levels of FSH also had elevated LH levels. Groups with severe seminiferous tubule failure (eg, Sertoli Cell Only syndrome or high FSH levels) showed an inverse correlation between LH and testosterone levels. In contrast, groups with milder forms of seminiferous tubule disorders (mild hypospermatogenesis, or FSH levels in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

1989
1989
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 14 publications
1
14
0
Order By: Relevance
“…Dysfunction of Sertoli cells, including inhibin secretion, might in turn cause increased levels of FSH. Furthermore, positive correlation between the FSH and LH levels of males has been reported [21,22], since secretion of these gonadotropins shares a common regulatory system. Taken together, the hyperplasia of Leydig cells in the repro22/repro22 mouse might be caused by dysfunction of Sertoli cells that results in elevated secretion of both FSH and LH; however, measurement of the FSH, LH and inhibin levels in mutant mice is necessary to prove this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Dysfunction of Sertoli cells, including inhibin secretion, might in turn cause increased levels of FSH. Furthermore, positive correlation between the FSH and LH levels of males has been reported [21,22], since secretion of these gonadotropins shares a common regulatory system. Taken together, the hyperplasia of Leydig cells in the repro22/repro22 mouse might be caused by dysfunction of Sertoli cells that results in elevated secretion of both FSH and LH; however, measurement of the FSH, LH and inhibin levels in mutant mice is necessary to prove this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Testosterone A solid-phase assay incorporating l25I-labelled testos¬ terone was employed. The interassay variations were 5-2 and 7-2% at concentrations of 8-8 and 19-5 nmol/1 (Morrow, Baker & Burger, 1986). The normal range for testosterone was 10-40 nmol/1.…”
Section: Inhibinmentioning
confidence: 97%
“…Morrow et al (24) reported comparable findings with a positive correlation between LH and testosterone in infertile men with low FSH values compared to those with high FSH levels, in whom the correlation was negative, suggesting heterogeneous causes for testicular malfunction. Interestingly, the group of patients with low inhibin B but normal FSH levels had significantly lower LH values in the presence of normal testosterone compared to other patients with a reduction in inhibin B levels.…”
Section: Discussionmentioning
confidence: 80%